2004
DOI: 10.1063/1.1739528
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic transport based on direct electrowetting

Abstract: Access to the full text of the published version may require a subscription. An integrated microfluidic system was fabricated which functions by deliberately manipulating interfacial tension. A distinctive characteristic of our system is the use of an array of adjacent, elongated, working electrodes and protruding polydimethylsiloxane open-flow channels. Microfluidic transport was realized directly on the bare gold electrode surface in the absence of an additional dielectric layer. By changing the potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Thus, the droplet can move, split, and merge in a controlled fashion. Several applications use EWOD as a main driving force: mass spectrometry [44,25], 'lab-on-a-chip' [33,18,20,32], particle separation/concentration control [10,41], auto-focus cell phone lenses [5], and colored oil pixels for laptops and video-speed smart paper [19,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the droplet can move, split, and merge in a controlled fashion. Several applications use EWOD as a main driving force: mass spectrometry [44,25], 'lab-on-a-chip' [33,18,20,32], particle separation/concentration control [10,41], auto-focus cell phone lenses [5], and colored oil pixels for laptops and video-speed smart paper [19,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…To avoid electrolysis, an insulating layer is usually inserted between the droplet and electrodes [4]- [6]. The applications of EWOD devices were discussed extensively in the literature, including microfluid transport [7], tunable optical fiber devices [8], rotating liquid micromotor [9], micro-injection [10], particle separation and concentration control [11]. Other studies focusing on the modeling of EWOD devices can be found in [3,5,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In the current research about EWOD, the phenomena on different dielectric materials are studied [7][8][9][10], and the applications in micro-devices are developed fast [11][12][13][14][15]. The interpretation about the principle of EW also attracts much attention [16][17][18].…”
Section: Introductionmentioning
confidence: 99%